Labyrinthine concussion following gunshot injury: A case report. (2nd July 2016) - Bogle, Jamie M.; Barrs, David; Wester, Matthew; Davis, Laurie; Cevette, Michael J
Abstract : Objective : Labyrinthine concussion due to a postauricular gunshot wound has not been well reported. Design : Retrospective chart review. Study sample : We describe an otherwise healthy 22-year-old male who received a gunshot wound to the left mastoid and subsequently reported hearing loss and rotational vertigo. Results : Audiometric testing demonstrated significant inverted scoop shaped sensorineural hearing loss. Vestibular diagnostic testing indicated a significant uncompensated left peripheral vestibulopathy. Imaging demonstrated no structural changes to the middle ear or labyrinth, suggesting that the auditory and vestibular losses noted on diagnostic examination were likely due to labyrinthine concussion. Conclusions : Labyrinthine concussion may lead to reduced vestibular reflex pathway following gunshot wounds to the temporal bone. Clinical presentation is likely to vary significantly among cases.